The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1136/thoraxjnl-2016-209889
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Pseudomonas aeruginosa in an unsegregated bronchiectasis cohort sharing hospital facilities with a cystic fibrosis cohort

Abstract: While (PA) cross-infection is well documented among patients with cystic fibrosis (CF), the equivalent risk among patients with non-CF bronchiectasis (NCFB) is unclear, particularly those managed alongside patients with CF. We performed analysis of PA within a single centre that manages an unsegregated NCFB cohort alongside a segregated CF cohort. We found no evidence of cross-infection between the two cohorts or within the segregated CF cohort. However, within the unsegregated NCFB cohort, evidence of cross-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 11 publications
(10 reference statements)
5
22
0
Order By: Relevance
“…Our results found that no major Australian CF shared P. aeruginosa strains were detected in our current cohort. In fact, our study found no evidence of shared P. aeruginosa strain infections, which is in keeping with the published data that shared P. aeruginosa strains are uncommon in patients with bronchiectasis or COPD . The P. aeruginosa strains detected in our study are commonly found in other niches, such as the natural environment and non‐CF infections .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results found that no major Australian CF shared P. aeruginosa strains were detected in our current cohort. In fact, our study found no evidence of shared P. aeruginosa strain infections, which is in keeping with the published data that shared P. aeruginosa strains are uncommon in patients with bronchiectasis or COPD . The P. aeruginosa strains detected in our study are commonly found in other niches, such as the natural environment and non‐CF infections .…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrates that patients with bronchiectasis and COPD can release aerosols containing viable P. aeruginosa during coughing; however, no shared strains of P. aeruginosa respiratory infection were detected in study participants. Our results support the published data that cross-infection of P. aeruginosa affects a minority of patients with bronchiectasis [14][15][16] and provides much needed evidence to understanding cross-infection in bronchiectasis, which was highlighted as a research priority in a recent review. 30 Whilst we have demonstrated that aerosol transmission is an unlikely transmission route, it is worth noting that the participants selected for the study were all low producers 26 of P. aeruginosa cough aerosols and also that the study participants had very few opportunities for transmission events to occur during hospital visits, thus reducing the risk of potentially being exposed to each other's cough aerosols.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations